A Complementary Low Schottky Barrier Nonvolatile Bidirectional Reconfigurable Field Effect Transistor Based on Dual Metal Silicide S/D Contacts - Liu Xi; Ya Wang; Meile Wu; Lin Qi; Mengmeng Li; Shouqiang Zhang; Xiaoshi Jin (IEEE Access)
In this work, a high-performance nanoscale complementary low Schottky barrier (CLSB) nonvolatile bidirectional reconfigurable field effect transistor (NBRFET) based on dual metal silicide source/drain (S/D) contacts (CLSB-NBRFET) is proposed. It is designed with Source floating gate (SFG) and drain floating gate (DFG) and adopts two kinds of metal silicide contacts to form complementary low Schottky barrier both between the S/D electrodes and the conduction band of silicon and between the S/D electrodes and the valence band of silicon at the same time. Instead of a program gate (PG) of conventional BRFET which needs independent power supply, the SFG and DFG of the proposed CLSB-NBRFET can be programmed by the CG itself. Thereafter, the interconnection can be simplified. The nonvolatile reconfigurable function is also realized. The type of charge stored in both SFG, and DFG decides the conduction type of the CLSB-NBRFET. Due to that there is a coupling effect between the effective voltages of SFG /DFG and the control gate (CG) voltage ( $\text{V}_{CG}$ ), the effective voltages of SFG and DFG can be decreased in the reverse biased state, and the reverse leakage current can be reduced. Besides, the dual metal silicide S/D contacts help to largely improve the forward current in both N mode and P mode comparing to conventional BRFET. Therefore, the scale of CLSB-NBRFET simplify the interconnection complexity and improve the characterization of BRFET. The scale of CLSB-NBRFET can be reduced to nanoscale while maintain high performance. The physical mechanism of the proposed CLSB-NBRFET has been analyzed in detail. The device performance has been compared with conventional BRFET. The influence of the amount of charge to the device performance has also been discussed in detail.